An Evaluation of PROMIS in Patients With Primary or Metastatic Spine Tumors. Issue 10 (15th May 2019) - Bernstein, David N.; Bakhsh, Wajeeh; Papuga, Mark Owen; Menga, Emmanuel N.; Rubery, Paul T.; Mesfin, Addisu
Abstract : Study Design: Retrospective evaluation of prospectively collected data. Objective: In spine tumor patients: i) to assess the correlation of Patient-reported Outcomes Measurement Information System (PROMIS) physical function (PF), pain interference (PI), and Depression scores with Oswestry Disability Index (ODI) and Neck Disability Index (NDI) scores; and ii) to assess ceiling and floor effects of PROMIS PF, PI, and Depression domains and the ODI/NDI. Summary of Background Data: There remains no widely used patient-reported outcome (PRO) instrument for spine tumor patients. PROMIS, a universal PRO tool, may add notable value to patient care. A paucity of work exists comparing PROMIS to legacy PRO tools in primary and metastatic spine tumor patients. Methods: Patients confirmed to have a primary or metastatic spine tumor were asked to complete PROMIS PF, PI, and Depression domains and either an ODI or NDI questionnaire between May 2015 and December 2017. Pearson correlation coefficients (r) were calculated. Ceiling and floor effects were determined. P < 0.05 was significant. Results: Eighty unique visits from 51 patients with spine tumors (44 metastatic/67 visits; 7 primary/13 visits) met our inclusion criteria. A strong correlation existed between PROMIS PI and the ODI/NDI in both primary and metastatic tumor patient subgroups (range, r = 0.75–0.86, P < 0.05). PROMIS PF and the ODI/NDI demonstrated a strong correlation among all patients (r = –0.75, P < 0.05) and in the metastatic disease subgroup (r = –0.78, P < 0.05). A strong correlation existed between PROMIS Depression and the ODI/NDI in the primary tumor subgroup (r = 0.79, P < 0.05). PROMIS Depression demonstrated the largest floor effect (13.6%); there were similar ceiling effects. Conclusion: PROMIS PF and PI domains correlate well with the ODI/NDI in spine tumor patients and have a similar ceiling effect but decreased floor effect. PROMIS Depression was not as well captured, except in the primary tumor subgroup. Level of Evidence: 2 Abstract : This retrospective review of prospectively collected data analyzes the correlation between PROMIS domains and the Oswestry Disability Index/Neck Disability Index in spine tumor patients, as well as ceiling/floor effects. This study suggests PROMIS captures similar outcomes to static, traditional patient-reported outcome (PRO) tools and may be used in this population.